Kemampuan Adaptasi Psikososial dengan Kemunculan Perilaku bermasalah pada Siswa Sekolah Dasar - Yuli Fitria (Jurnal Riset Madrasah Ibtidaiyah, 2022)
Students’ misbehavior that occurs in the school environment is a refraction of social cognition processes that can interfere with psychosocial development which can have a negative impact on adulthood. Poor psychosocial adaptation is suspected to be one of the causes of problematic behavior emergence, so preventive measures are needed. This study aimed to reveal the correlation between psychosocial adaptability and the emergence of misbehavior. The research subjects were 108 students in the first and second grades at three elementary schools in Singojuruh District, Banyuwangi. The sampling technique used purposive sampling. The research instrument used the SSRT (Social Skill Rating Scale) and SDQ (Strength and Difficulties Questionnaire). Data analysis used simple regression analysis. The results showed that there was a significant negative correlation (r = -0,271, p = 0.012). It means that the higher the psychosocial adaptability, the smaller the emergence of misbehavior and vice versa. Based on the analysis result, it can be concluded that developing students' psychosocial adaptability can be used as a method to prevent the emergence of misbehavior.